PENGARUH LAMA PEMERAMAN TERHADAP NILAI BAHAN KERING, BAHAN ORGANIK DAN SERAT KASAR PAKAN KOMPLIT BERBASIS PUCUK TEBU TERFERMENTASI MENGGUNAKAN EM-4 - Ahmad Iskandar Setiyawan; Nurita Thiasari (Universitas Tribhuwana Tunggadewi, 2016)
Total Mixed Ration (TMR) is a technology development of silage. The aims of TMR is making feed to keep from microbia, but also contains nutrients to supply nutriens requirement.In the fermentation process have major obstacles in the long ripening. In the long period of the fermentation process which make decrease the nutrient content of feed due to used of feed nutrients by the microbes. TMR research still not optimal so make this research become important to conduct about optimal microbes in the fermentation process of the nutrient content in the manufacture of Total Mixed Ration especially based shoot sugarcane.The method of this research used completely randomized design (CRD) with directional pattern. This research used 2 treatments, the inoculum EM4 (P1) and without inoculum (P0); with the curing time of 0, 7, 14, and 21 days.The results showed that the use of inoculum EM4 in TMR shoot sugarcane can decrease crude fiber content of 29.31% to 24.9% at day 7 compared with the controls, which had decreased on day 21. In the dry matter (BK) there are significantly differences (p